2022
DOI: 10.1038/s41467-022-34569-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneously tuning interlayer spacing and termination of MXenes by Lewis-basic halides

Abstract: The surface and interface chemistry are of significance on controlling the properties of two-dimensional transition metal carbides and nitrides (MXenes). Numerous efforts have been devoted to the regulation of Ti3C2Tx MXene, however, tuning interlayer spacing and surface halogen termination of other MXenes (besides Ti3C2Tx) is rarely reported while demanded. Here we propose a Lewis-basic halides treatment, which is capable of simultaneously engineering the interlayer spacing and surface termination of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…Very recently, Zhang et al reported the synthesis of Ti 3 C 2 Br x MXene through CuCl 2 etching of Ti 3 AlC 2 precursor and subsequent termination substitution in AlBr 3 /NaBr/KBr eutectic molten salts [128]. When the molar ratio of AlBr 3 is lower than 50%, the AlBr 3 /NaBr/ KBr molten system with plenty of naked Na + , K + and Br − demonstrates strong Lewis basicity.…”
Section: Terminations Regulationmentioning
confidence: 99%
“…Very recently, Zhang et al reported the synthesis of Ti 3 C 2 Br x MXene through CuCl 2 etching of Ti 3 AlC 2 precursor and subsequent termination substitution in AlBr 3 /NaBr/KBr eutectic molten salts [128]. When the molar ratio of AlBr 3 is lower than 50%, the AlBr 3 /NaBr/ KBr molten system with plenty of naked Na + , K + and Br − demonstrates strong Lewis basicity.…”
Section: Terminations Regulationmentioning
confidence: 99%
“…As shown in Figure a, the CV profiles are recorded at 0.2 mV s –1 to probe the sodiation/desodiation mechanism of the Ti 3 C 2 T x -700 electrode. In the first cathodic cycle, an irreversible reduction peak appears at 0.9 V and vanishes in subsequent sodiation processes, which is caused by SEI formation and electrolyte decomposition. , A cathodic peak corresponds to intercalation of Na + ions into MXene. , An anodic peak is ascribed to extraction of Na + ions from the MXene matrix. , In subsequent cycles, the almost overlapped curves imply that the Ti 3 C 2 T x -700 MXene anode exhibits high reversibility and stable cyclability.…”
Section: Na+ Storage Property Of Ti3c2t X Mxenementioning
confidence: 99%
“…2D materials have gained attention for emerging application fields in nanogenerators, desalination, energy, optoelectronics, electronics, electrocatalysis, etc. In particular, 2D transition-metal nitrides and carbides called MXenes are one of the growing families of 2D materials. They are summarized by the chemical formula M n +1 X n T x ( n = 1–3), where M is a transition-metal element (Ti, Cr, Nb, V, and so on), X represents nitrogen or/and carbon, and T x denotes surface terminations of −O, −OH, −F, or −Cl. Due to the rich diversity, tunable band gaps, mixed metallic-covalent nature of M–X and M–T x bonds, cross-scale microstructure, superior flexibility, and exposed surface for delaminated MXene nanosheets, abundant surface terminations, etc., MXenes have promise in a variety of fields, particularly in energy storage fields. , …”
mentioning
confidence: 99%
“…can be advantageous for energy storage. [28,76,89] The nature of electrolytes strongly affects the charge storage mechanism of MXenes. For instance, the pseudocapacitance of the MXene in an acidic electrolyte mainly originates from the surface-based redox reactions.…”
Section: Mxene: From Fundamental To Synthesis Property and Energy Sto...mentioning
confidence: 99%